2018
DOI: 10.20546/ijcmas.2018.705.138
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Bacteriuria in Pregnant Women - Study at a Tertiary Maternity care Hospital in Hyderabad

Abstract: Journal homepage: http://www.ijcmas.com Urinary Tract Infections (UTIs) commonly occurs in pregnancy, due to the morphological and physiological changes that take place in the genitourinary tract.Asymptomatic bacteriuria refers to the presence of bacteria in urine, and is a condition in which urine culture reveals a significant growth of pathogens that is greater than 10 5 bacteria/ml, but without the patient showing symptoms (Gilbert et al., 2005). The apparent reduction in immunity of pregnant women appears … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…To help achieve the required sample size and to facilitate the resource mobilization for the study site, the study was conducted in a government tertiary care hospital, Gandhi Hospital, Secunderabad, India, from February 2017 to February 2018. The study hospital receives walk-in patients mostly from the areas within and around Secunderabad and Hyderabad, which are twin cities in the state of Telangana, India with a combined population of nearly 700,000, and a reported prevalence of ASB in pregnancy as 18% [21] . Referred patients from even other districts of Telangana are also catered by the hospital since it is a tertiary care hospital.…”
Section: Methodsmentioning
confidence: 99%
“…To help achieve the required sample size and to facilitate the resource mobilization for the study site, the study was conducted in a government tertiary care hospital, Gandhi Hospital, Secunderabad, India, from February 2017 to February 2018. The study hospital receives walk-in patients mostly from the areas within and around Secunderabad and Hyderabad, which are twin cities in the state of Telangana, India with a combined population of nearly 700,000, and a reported prevalence of ASB in pregnancy as 18% [21] . Referred patients from even other districts of Telangana are also catered by the hospital since it is a tertiary care hospital.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, the higher tWBC in the present study confirms the value recently reported by Musa and colleagues (2016) among pregnant women undergoing antenatal care in a sister tertiary health institution in Sokoto. Whether the higher leucocytosis in the third trimester of pregnancy in our results was due to physiological leucocytosis of pregnancy (Wang et al, 2016;Malikarjun et al, 2018), even when a similar northern Nigerian average is lower could still be explained in possible differences in the stress (pregnancy and otherwise) which these groups of pregnant women undergo and for our study which focused only on the third trimester during which stress is expected to be more profound requires further research. Given that these study groups were from the different geo-political zones of Nigeria with their different culture and women lifestyles, and stress levels during pregnancy may be a possible explanation as pointed out to be a major factor in leukocytosis of pregnancy (Chandra et al, 2012).…”
Section: Discussionmentioning
confidence: 66%
“…Third trimester of pregnancy is associated with some form of stress including those arising from the rapidly growing foetus and uterus (Ciliberto andGertie, 1998, Kaur et al, 2014). This stress, together with some other factors of pregnancy require the body immune systems adjusting to meet up the challenges (Mor and Cardenas, 2010) and may be reflected in WBC profile seen as leucocytosis (Pughikumo et al, 2015, Gebreweld et al, 2018, Wang et al, 2016, Malikarjun et al, 2018Duru et al, 2016). This however, doesn't exclude the presence of some other reasons that may occasion leucocytosis in pregnancy such as infection (Ramsay, 2010;Serrano et al, 2011) or gestational diabetes mellitus (Pattanathaiyanon et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This was similar to a study conducted by Nahab et al done among pregnant women in Al Samawa City of Iraq, Rosana et al in a community health centre in Jakarta, Indonesia, and Rao in a tertiary maternity care hospital in Hyderabad. 19,25,26 On the contrary, fewer studies found K. pneumoniae as the dominant uropathogen. 27 After E. coli, Enterococcus species (19.7%), K. pneumoniae (16.7%) were the dominant pathogens in this study.…”
Section: Discussionmentioning
confidence: 99%